Xeroderma pigmentosum--Cockayne syndrome complex: a further case. - Hamel, B C (1996)
We report on a male patient born to healthy, first cousin, Moroccan parents. During the pregnancy growth retardation was observed. Birth weight, length, and OFC were all well below the 3rd centile. Facial anomalies, microphthalmia, cleft palate, small penis, and flexion contractures of large joints were noted. Cerebral MRI showed dysmyelination. The clinical course was characterised by feeding difficulties, growth failure, lack of development, photosensitivity, and death at 7 months. The main differential diagnoses were COFS syndrome and early onset Cockayne syndrome (CS). UV exposure of cultured fibroblasts showed inhibition of nucleic acids synthesis. Further DNA repair studies showed extreme cellular sensitivity to UV and xeroderma pigmentosum (XP)-like defective nucleotide excision repair (NER), which in combination with the clinical symptoms indicated the very rare XP-CS complex. Complementation analysis showed that the XPG gene is affected in this patient. In cases suspected of having COFS syndrome and early onset CS, extensive DNA repair studies are needed to reach the definitive diagnosis, thereby allowing reliable genetic counselling and prenatal diagnosis.